Tooling4G – Minimize the Airflow Generated Noise on Automotive HVAC Systems - Caseiro, J. F. (2021)
The main goal of this work is to assess the gain that can be obtained when considering High-Performance Computing (HPC) for solving complex industrial problems. To that end, a Heat, Ventilation and Air Conditioning (HVAC) system of an automobile is analysed by means of an Aero-Acoustic Computational Fluid Dynamics (CFD) analysis. The performances of the HPC Navigator from the University of Coimbra and a research workstation are compared using Ansys® Fluent. Results show that using the Navigator with 64 cores distributed equally on two nodes reduces by a factor of 12.3 the execution time when compared with a workstation limited to 4 cores. The use of HPC resources is extremely useful for Small and Medium Enterprises (SMEs) that don’t have the required hardware to solve this kind of problems, enabling an increase in productivity and reducing costs associated with shorter project stages